Fraud Triangle, Use of Information Technology, and Academic Dishonesty of Accounting Students: Testing Religiosity as a Moderator - Simbolon, Ramadona (PT. Riset Press International, 2025)
This study aims to analyze the influence of pressure, opportunity, rationalization, and the use of information technology on academic fraud and to examine the role of religiosity as a moderator. This research was conducted at the Islamic University of North Sumatra with accounting students as respondents. The sample was selected using purposive sampling with the criteria of accounting students who had previously taken an exam, resulting in 162 respondents. The data obtained will be analyzed using Moderated Regression Analysis with an interaction test approach. This research adopts the fraud triangle theory approach into the realm of education at one Islamic University, which has cultural and academic environmental characteristics based on Islam. Additionally, this research adds the variable of information technology usage, which is relevant to current digital developments, and tests religiosity as a moderator, providing a psychological and moral perspective on students' tendency to cheat. The research findings revealed that rationalization and the use of information technology have a positive and significant impact on academic dishonesty, while pressure and opportunity do not. The interesting findings of this study indicate that religiosity acts as a moderator in the relationship between pressure and rationalization toward academic dishonesty. Educational institutions, particularly accounting study programs, need to instill and internalize religious and ethical values in the learning process, thereby building and strengthening an academic culture of integrity and reducing tolerance for various forms of justification that can encourage cheating.